Preparation of Novel Nanomaterial and Its Application in Food Industry - Wu, Hong; Zhang, Hui (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nanotechnology has offered a wide range of opportunities for the development and application of structures, materials, or systems with new properties in the food industry in recent years. The developed nanomaterials could greatly improve not only food quality and safety but also the foods' health benefits. Therefore, the great potential of nanomaterial has provided a new perspective for researchers to dive deep into the material at the nano level. It is essential to further come up with novel techniques, methods, and products that have a direct application to nanotechnology in food science. This Special Issue aims to provide an overview of the current and projected outcomes made on nanoscience and nanotechnology fields, from nanomaterials design, conception and characterization to its application in a variety of food-related industries. Researchers are invited to submit their up-to-date original research articles, review works, and short communications to this Foods Special Issue: "Preparation of Novel Nanomaterial and its Application in Food Industry"